O Quinhão da Vila de Pedrinhas (Santarém Novo, Pará) e o ensino de História: a vivência como estratégia de aprendizagem - ALMEIDA, Eula Regina Cidade (2018)
The present research points to the importance of local history in the school curriculum and the valorization of memory for the understanding and rescue of its historical and social identity. The relevance of this work lies in the understanding of the development of methodologies that favor a teaching of History committed to the insertion of local history in the classroom, valuing the daily life of the students. The purpose of this article is to expose the importance of local history in the teaching of history, having as an exposition the analysis of Quinhão, a common practice in Vila de Pedrinhas, located in the northeast region of the state of Pará Vila de Pedrinhas, reflecting within the curriculum of the college Teaching Core Small Prince located in Ananindeua. In this way, it was possible to perceive the importance of the many practices that still exist in villages and how they can be excellent means for teaching and learning in the discipline of history. In the face of this evidence, we observe that local history can contribute to the feeling of identity and belonging, and that practices such as these exist in Pedrinhas, must be known by the student community, as they demonstrate the continuities and ruptures of a past that often for students is only past, however, are characteristics that are part of a construction in which all participate, can not be ignored or forgotten, as a result there was the promotion of an activity in the classroom.